2012
DOI: 10.1177/0022034512449463
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Plus Functionalized β-TCP

Abstract: With more than 50 years of clinical success, fluoride serves as the gold standard agent for preventing tooth decay. In particular, the action of fluoride facilitates saliva-driven remineralization of demineralized enamel and alters solubility beneficially. Still, tooth decay remains problematic, and one way to address it may be through the development of new mineralizing agents. Laboratory and clinical studies have demonstrated that the combination of fluoride and functionalized β-tricalcium phosphate ( fTCP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…The coating breaks when it is applied to the tooth surface. Calcium, phosphate, and fluoride ions become available to promote remineralisation through the tooth’s uptake of these ions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The coating breaks when it is applied to the tooth surface. Calcium, phosphate, and fluoride ions become available to promote remineralisation through the tooth’s uptake of these ions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Significantly Karlinsey et al [ 25 , 32 34 ] have reported a synergistic relationship between fTCP and fluoride with regard to enamel remineralisation; enamel that is remineralised through a fluoride/fTCP combination demonstrates significantly greater surface and subsurface rehardening following pH cycling compared to that achieved by fluoride application alone. Notably, the results of the present study suggest that this remineralisation synergy between fluoride and fTCP may also produce a benefit in terms of enhancing dentine tubule occlusion; the two test groups that utilised Clinpro Tooth Crème (950 ppm F) demonstrated a greater level of sensitivity relief for all stimuli except the hypertonic test at 10 weeks (group C) in comparison to the group using Colgate Total, despite the fact that Colgate Total contains a greater concentration of fluoride ions (1000 ppm F).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is notable, as not only there is limited data demonstrating that ≤1000 ppmF dentifrices can effectively reduce dentine sensitivity, but the availability of such a dentifrice could lower the cost and complexity of “at home” treatment undertaken by a patient suffering from dentine sensitivity, a dentifrice containing ≤1000 ppmF being appropriate for the control of dental caries in low caries risk patients [ 23 , 24 ]. Importantly, while assessment of the anticaries benefits of this dentifrice has been reported [ 25 ], no assessment of the efficacy of this dentifrice to reduce dentine sensitivity in vivo has taken place.…”
Section: Introductionmentioning
confidence: 99%
“…CPP-ACP forms aggregates that prevent calcium phosphate precipitation, demineralization and promotes remineralization (14). CPP-ACP has been shown to have anti-anticariogenic activity in in vitro experiments, in animals and in situ in humans (15) , (16) , (17). MI Varnish (GC Tooth Mousse; GC Corporation, Tokyo, Japan) also contains sodium uoride 5%.…”
Section: Introductionmentioning
confidence: 99%